Kesejahteraan Sosial Buruh Nelayan Tambak di Gampong Pulo Kecamatan Bandar Dua Kabupaten Pidie Jaya - Shifa, Ashshifa Annur (JAROW: Journal of Ar-Raniry on Social Work, 2024)
Fishing pond workers are poor people who do not have their own ponds so they have to work for wages for other people who have ponds. They are people who have no other income. In Gampong Pulo there are several families who work as pond fishermen, which they have done for a long time, this work can only support their livelihood. Based on this, the researcher wants to know and explain the level of welfare of pond fishing workers. To find this, researchers used qualitative research with descriptive methods. The subjects used were 12 respondents with certain criteria using a purposive sampling technique. To obtain data, researchers conducted observations, interviews and documentation, and analyzed using data reduction, data presentation, decision making and verification. The research results show that the welfare of pond fishing workers is still low, the reason is that the sustainability of the pond business is influenced by weather factors, pond owners, global economic conditions, and so on. To improve the welfare of pond fishing workers, it is necessary to make continuous efforts to optimize the potential of fishery resources in ponds and increase the capacity for adaptation to environmental changes as well as training and working capital to improve the skills and economic level of fishing workers.